Menyelami Esensi Sifat Dasar Manusia Terhadap Pembentukan Karakter Anak Usia Dini - Ubaidillah, Ubaidillah; Anindya Fadiatur Rohmah, Nadin; Sari, Yulia; Zein, Muhammad; Ummah, Ishomul (Program Studi Pendidikan Islam Anak Usia Dini, 2023)
The essence of human nature lies within humans themselves. Humans have a crucial and fundamental goal of education to guide human life. Early Childhood Education (ECE) plays a significant role in shaping children's characters from an early age. This research aims to examine the factors contributing to the formation of children's characters from an early age. The research method employed is qualitative research, oriented towards a descriptive qualitative approach, which relies on natural settings as direct sources of data and where the researcher serves as the key instrument. Factors such as understanding human nature, implementing integrated character education, and social environment influence significantly the development of ECE characters. The 7 fitrah anak program is one powerful approach to character education, emphasizing fundamental moral values. Despite the acknowledged importance of character education, challenges such as adjusting educational approaches to individual children's needs still need to be addressed. Through collaboration among the government, educational institutions, families, and society, and by understanding the interaction between the development of ECE characters and children's human nature, we can create an optimal educational environment for holistic child development. Therefore, a strategy of education based on human nature becomes crucial in shaping positive characters in early childhood, aiming to provide them with a strong foundation for success in the future.